Nutritional effects of beef connective tissue characteristics and eating qualities - Wu, J.J.; Hunt, Melvin C.; Kropf, Donald H.; Allen, Dell M.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station, 2011)
We compared taste panel and connective tissue characteristics of beef fed a high energy diet with beef fed grass. The high energy diet produced higher USDA quality and yield grades, more rapid weight gain, and increased connective tissue collagen synthesis arid breakdown. But, it did not consistently improve taste panel and shear characteristics over grass-feeding.
Keywords: Beef; Quality grade; Yield grade; Gain